2018
DOI: 10.3892/ol.2018.8369
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of long non-coding RNAs in human gastric cancer

Abstract: Abstract. Abnormal regulation of long non-coding RNAs (lncRNAs) appears to be a primary feature of numerous types of human cancer. However, the association between the dysregulation of lncRNAs and functional alterations in gastric cancer (GC) remains unclear. In previous studies, we applied microarray and bioinformatics analyses to screen for key lncRNAs from the tumor tissues and matched adjacent non-tumor tissues of 10 patients with GC. There were seven key lncRNAs demonstrated to be significantly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Down-regulation of XLOC_010588 inhibited the invasion and migration of colorectal cancer cells through regulating genes associated with EMT [14]. Furthermore, TUSC8 (LINC01071) showed consistent down-regulation in gastric cancer (GC) compared with adjacent non-tumor tissues and was significantly correlated with the age and gender of the GC patients, respectively [15,16]. However, apart from the above studies, the biological functions and underlying molecular mechanisms of TUSC8 with respect to breast cancer remain largely unclear.…”
Section: Agingmentioning
confidence: 99%
“…Down-regulation of XLOC_010588 inhibited the invasion and migration of colorectal cancer cells through regulating genes associated with EMT [14]. Furthermore, TUSC8 (LINC01071) showed consistent down-regulation in gastric cancer (GC) compared with adjacent non-tumor tissues and was significantly correlated with the age and gender of the GC patients, respectively [15,16]. However, apart from the above studies, the biological functions and underlying molecular mechanisms of TUSC8 with respect to breast cancer remain largely unclear.…”
Section: Agingmentioning
confidence: 99%
“…Similarly, investigation of MCPH1/BRIT1 frameshift mutations in gastric cancer found that 11% (4/34) of cases with high MSI contained MCPH1/BRIT1 frameshift mutations compared to (0/45) with low MSI (49). Another study characterising long non-coding RNAs (lncRNA) in gastric cancer identified over-expression of 6 key lncRNA including MCPH1/BRIT1 antisense RNA 1 (CTD-2541M15) which were associated with invasion and metastasis (58).…”
Section: Mcph1/brit1 In Gastric Carcinomamentioning
confidence: 99%